Dimensions and outcomes of experience quality in tourism: The case of Port wine cellars. (July 2016) - Fernandes, Teresa; Cruz, Mariana
Abstract: Ever since the notion that consumption has an experiential dimension, experience and its impact on business is receiving increased attention. Therefore, understanding experience quality, its drivers and outcomes becomes crucial, especially when experiences are the core of the service offering such as in tourism. However, research on tourism experiences remains sparse and largely conceptual. We develop a higher-order model of experience quality, validated in the wine tourism industry, outlining relevant dimensions and outcomes. Results support the six-dimensional structure of experience quality and its impact on loyalty, satisfaction and word-of-mouth. Overall, we validate a holistic multi-dimensional measure of experience quality and examine key nomological relationships, with important implications for tourism managers.